An Extraordinary Case of Autoimmune Polyendocrinopathy-Candidiasis-Ectodermal Dystrophy (APECED) Syndrome Misdiagnosed as Juvenile Idiopathic Arthritis on Admission - Gulcin Aytac; Burcu Guven; Ilyas Aydin; Ezgi Topyildiz; Ayca Aykut; Asude Durmaz; Neslihan Edeer Karaca; Guzide Aksu; Necil Kutukculer (Case Reports in Immunology)
Background. APECED is a syndrome characterized by autoimmune polyendocrinopathy, candidiasis, and ectodermal dystrophy. The most observed clinical findings are chronic mucocutaneous candidiasis, hypoparathyroidism, and autoimmune adrenal insufficiency. Case Presentation. A three-year-old male patient was admitted with classical signs of juvenile idiopathic arthritis and treated with nonsteroidal anti-inflammatory drugs. During follow-up, signs of autoimmunity, candidiasis, nail dystrophy, and onychomycosis were observed. The parents were consanguineous, and targeted next-generation sequencing was performed. A homozygous mutation in the AIRE gene SAND domain (c.769C > T, p.Arg257Ter) was detected, and the patient was diagnosed with APECED syndrome. Conclusion. Inflammatory arthritis is rarely described in association with APECED and is often misdiagnosed as juvenile idiopathic arthritis. In APECED cases, nonclassical symptoms such as arthritis may occur before developing classical symptoms and considering the diagnosis of APECED in patients with CMC and arthritis is useful for early diagnosis before development of complications and management of disease.